"Paratrigeminal" paralysis of the oculopupillary sympathetic system. Issue 3 (1st March 2002) - Goadsby, P J
Abstract : Raeder described five patients with mixed features of trigeminal nerve pathology and oculosympathetic impairment, with or without other cranial nerve lesions. This constellation of clinical features drew the original author's attention to the paratrigeminal region as a likely site for the causative lesion in this syndrome. An analysis of the anatomy of the oculosympathetic innervation supports the view that a restricted lesion in the middle cranial fossa might cause the syndrome of trigeminal nerve involvement, neuralgic pain or sensory change, with ptosis or miosis, or both, but no anhidrosis. Such a paratrigeminal oculosympathetic syndrome (POSS) usefully reminds clinicians to pursue vigorously possible lesions of the middle cranial fossa with careful, and possibly repeated, imaging studies. Attaching the eponym Raeder's syndrome or Raeder's paratrigeminal neuralgia to this syndrome adds nothing valuable to the anatomical description (POSS), which might be preferred for clarity.